Current mode multi scroll chaotic oscillator based on CDTA - Lin, Yuan; Gong, Junhui; Yu, Fei; Huang, Yuanyuan (Frontiers in Physics, 2023)
In this paper, a current mode chaotic oscillation circuit based on current differential transconductance amplifier (CDTA) is proposed. This proposed circuit fully utilizes the advantages of CDTA: a current input and output device with a large dynamic range, virtual ground at the input, extremely low input impedance, and high output impedance. The linear and nonlinear parts of the proposed circuit operate in current mode, enabling a true current mode multi scroll chaotic circuit. Pspice simulation results show that the current mode chaotic circuit proposed can generate multi scroll chaotic attractors.